The Importance of Factors Affecting the Entry of Entrepreneurial Subjects to Organic Farming in the Czech Republic - Stojanová, Hana; Blašková, Veronika; Lněničková, Michaela (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2018)
The aim of the article is to identify the key factors influencing the entry of entrepreneurial subjects into the sphere of organic farming in the Czech Republic. Primary data for the research was obtained from a questionnaire survey carried out in 2016 through an internal communication system of the PRO BIO Association, comprising 481 operators in the field of organic farming in the Czech Republic. The research questions mainly concerned the reason for entering the sphere of organic farming, and what influenced this decision, the motivation of entrepreneurs to stay in organic farming and what could possibly be the reason for their departure from this sector of business. Another part of the research questions related to the knowledge about organic farming in the establishment of their business. a combination of factors that are important in deciding on entry into the industry and subsequent stay was found.